Cover Picture: Realizing the Storage of Pressurized Hydrogen in Carbon Nanotubes Sealed with Aqueous Valves (Energy Technol. 5‐6/2013). Issue 5 (20th June 2013) - Tang, Changyu; Man, Changzhen; Chen, Yungui; Yang, Fei; Luo, Linshan; Liu, Zhi‐Feng; Mei, Jun; Lau, Woon‐Ming; Wong, Ka‐Wai
<x xml:space="preserve">Abstract</x> Nanoscale Tanks for Pressurized Hydrogen Storage: Hydrogen has long been recognized as a clean and renewable fuel with great promise, as water is the only by‐product from the consumption of abundantly available hydrogen fuel. However, the practical utilization of hydrogen fuel is severely restricted by the lack of a viable solution for hydrogen storage. In automotive applications, the use of heavy stainless‐steel cylinders of pressurized hydrogen not only reduces the energy efficiency substantially, but also poses a serious safety issue. The Communication by Ka‐wai Wong and colleagues at Chengdu Green Energy and Green Manufacturing R & D Center on page page 309 demonstrates that single‐walled carbon nanotubes can be used to store pressurized hydrogen by using aqueous valves to seal the ends. The storage and release of hydrogen with these nanocapsules was thermally controlled by heating the nanotubes above the melting temperature of the ice. In this proof of concept, hydrogen was stored at a pressure of 5.0 MPa without significant leakage. Preliminary estimation reveals that an attractive gravimetric energy efficiency as high as 9 % would be achieved at a storage pressure of 1 GPa hydrogen.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>